Law enforcement of the abuse of subsided fuel based on law number 22 of 2001 concerning oil and natural gas - Imam Subiyanto (Journal of Law Science, 2023)
Misuse of subsidized fuel is an illegal act that can harm others. The research objective is to analyze law enforcement strategies against the abuse of subsidized fuel based on Law Number 22 of 2001 concerning Oil and Gas. This research is normative legal research with a case approach. The misuse of subsidized fuel based on Law Number 22 of 2001 concerning Oil and Gas is carried out in a preventive and repressive manner referring to Article 53 and Article 55 of Law Number 22 of 2001 concerning Oil and Gas. The police as investigators in cases of criminal acts of misuse of subsidized fuel take steps including receiving reports/complaints; Report Development (BAP Making); Summoning Witnesses and Evidence; Examination of Suspects; and Delegation of the suspect's case files and evidence to the Attorney General's Office and the Court as regulated in the Criminal Procedure Code.